Optimal solution of engineering design problems through differential gradient evolution plus algorithm: a hybrid approach. (10th January 2022) - Tabassum, Muhammad Farhan; Akgül, Ali; Akram, Sana; Hassan, Saadia; Saman; Qudus, Ayesha; Karim, Rabia
Abstract: It is very necessary and applicable to optimize all disciplines. In practical engineering problems the optimization has been a significant component. This article presents the hybrid approach named as differential gradient evolution plus D G E + algorithm which is the combination of differential evolution gorithm and gradient evolution ( G E ) algorithm. D E was used to diversify and G E was used for intensification with a perfect equilibrium between exploration and exploitation with an improvised distribution of dynamic probability and offers a new shake-off approach to prevent premature convergence to local optimum. To describe the success, the proposed algorithm is compared to modern meta-heuristics. To see the accuracy, robustness, and reliability of D G E + it has been implemented on eight complex practical engineering problems named as: pressure vessel, belleville spring, tension/compression spring, three-bar truss, welded beam, speed reducer, gear train and rolling element bearing design problem, the results revealed that D G E + algorithm can deliver highly efficient, competitive and promising results.